The Domestic Investment, Local Government Revenue and Government Expenditure in the Education Sector - Endang Sri Wahyuni; Ady Soejoto; Norida Canda Sakti (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2019)
This research aimed to analyze the effect of domestic investment and local government revenue toward government expenditure in the education sector. This research uses secondary data obtained from Central Bureau of Statistics in Indonesia and Local Educational Balance-Departement of Education and Culture. The analysis technique used is panel data regression analysis with cross section 34 provinces and time series for 2014-2017. The results showed that partially, domestic investment and local government revenue had a significant affect on government expenditure in the education sector. Meanwhile simultaneously, it shows that domestic investment and local government revenue had a significant affect on government expenditure in the education sector. These findings indicate that the level of education expenditure can be influenced by both domestic investment and local government revenue.